Self-control, self-regulation, and doping in sport: A test of the strength-energy model - Chan, D. K. C.; Lentillon-Kaestner, V.; Dimmock, J. A.; Donovan, D. J.; Keatley, D. A.; Hardcastle, S. J.; Hagger, M. S. (Journal of Sport & Exercise Psychology, 2015)
We applied the strength-energy model of self-control to understand the relationship between self-control and young athletes` behavioral responses to taking illegal performance-enhancing substances, or "doping." Measures of trait self-control, attitude and intention toward doping, intention toward, and adherence to, doping-avoidant behaviors, and the prevention of unintended doping behaviors were administered to 410 young Australian athletes. Participants also completed a "lollipop" decision-making protocol that simulated avoidance of unintended doping. Hierarchical linear multiple regression analyses revealed that self-control was negatively associated with doping attitude and intention, and positively associated with the intention and adherence to doping-avoidant behaviors, and refusal to take or eat the unfamiliar candy offered in the "lollipop" protocol. Consistent with the strength-energy model, athletes with low self-control were more likely to have heightened attitude and intention toward doping, and reduced intention, behavioral adherence, and awareness of doping avoidance.